A Neuron‐Glia Co‐culture System for Studying Intercellular Lipid Transport. Issue 1 (9th August 2019) - Ioannou, Maria S.; Liu, Zhe; Lippincott‐Schwartz, Jennifer
Abstract: Neurons and glia operate in a highly coordinated fashion in the brain. Although glial cells have long been known to supply lipids to neurons via lipoprotein particles, new evidence reveals that lipid transport between neurons and glia is bidirectional. Here, we describe a co‐culture system to study transfer of lipids and lipid‐associated proteins from neurons to glia. The assay entails culturing neurons and glia on separate coverslips, pulsing the neurons with fluorescently labeled fatty acids, and then incubating the coverslips together. As astrocytes internalize and store neuron‐derived fatty acids in lipid droplets, analyzing the number, size, and fluorescence intensity of lipid droplets containing the fluorescent fatty acids provides an easy and quantifiable measure of fatty acid transport. © 2019 The Authors.